Pemberdayaan Masyarakat Gandaria Utara dalam Menciptakan Lingkungan yang Produktif serta Lingkungan Hijau dan Asri - Martini; Windarto; Samsinar; Prasetio, Tio; Hariyani, Reni (Artinara, 2022)
Community service activities are a form of implementation of one of the Tri Dharma of Higher One way to implement one of the three dharmas of higher education is to carry out community service activities. This activity was carried out in December 2021 at the North Gandaria Village, Kebayoran Baru District, South Jakarta. The theme of this activity is Creating a Productive Environment and a Green and Beautiful Environment. With the targets of the programs that have been designed, it is hoped that they will be able to build interest in the local community to continue to be aware of the environment and be able to develop and utilize their potential. There are still many programs that have been planned by the North Gandaria Village which have not been realized, so that with this community service activity it can help carry out the programs that have not been realized. The existing programs in this community service activity also adjust to existing programs in the kelurahan but have not been realized. The results of this community service activity are the planting of green vines in the vicinity of the North Gandaria sub-district, the rearrangement of the RPTRA environment so that children feel more comfortable playing in the area, education about waste and its management as well as the distribution of masks and hand sanitizer to users. roads and surrounding communities.